Importance of cancer cell culture - Ashour, Abdelkader Elbadawy Abbas (2018)
Cell culture is practiced extensively throughout the world today. The techniques required to allow cells to grow & be maintained outside the body have been developed throughout the 20th century.Since the publication of the first human cancer cell line, HeLa(in 1951), thousands of cell lines representing most of the spectrum of human cancer have been derived